Os consumidores nas redes sociais: as suas motivações e as percepções das marcas - Oliveira, Soraia Inês Pires de (2018)
Submitted by Susana Santos (susana.santos@universidadeeuropeia.pt) on 2018-05-29T11:51:41Z No. of bitstreams: 1 TeseSoraiaOliveiraV2.pdf: 13155739 bytes, checksum: 631f7d660cc92c624b40fe1ce8adbbde (MD5)